Variation in the Melampyrum sylvaticum group - Těšitel, Jakub (Jihočeská univerzita, 2007)
This study deals with morphological variation in the Melampyrum sylvaticum group (Orobanchaceae). Populations of the Hercynian Massif, Western and Eastern Carpathians were investigated using both conventional and geometric morphometric methods. Individual morphological characters were evaluated in detail. Preliminary taxonomic concept of the group is presented. Biogeographical context of detected morphological variation is discussed.
Variation in the Melampyrum sylvaticum group
Keywords: biogeography; Carpathians; Central Europe; geometric morphometrics; Hercynian Massif; Melampyrum; morphology; sliging semilandmarks; taxonomy; thin plate spline; variation; biogeography; Carpathians; Central Europe; geometric morphometrics; Hercynian Massif; Melampyrum; morphology; sliging semilandmarks; taxonomy; thin plate spline; variation